Integrating Governance, Technical Controls, and Agile Practices: A Multi Layered Risk Management Framework for High Technology Projects - Hermansyah, Heri; Zakaria, Ricky Muhamad (Novatio : Journal of Management Technology and Innovation, 2024)
High technology project environments present a complex landscape of interdependent risks spanning governance, technical, and operational domains. This study examines the integration of governance structures, domain specific technical controls, and agile risk management practices to address these multifaceted challenges. The research highlights the strategic synergy between frameworks such as ISO 31000, ISO/IEC 27005, NIST SP 800 53, and the NIST AI RMF, combined with agile techniques like SAFe ROAM, to create a comprehensive, layered risk management architecture. This approach enables precise risk identification, robust mitigation planning, and responsive adaptation to rapidly evolving technological and market conditions. The methodology involved analyzing best practices in cross framework integration, risk mapping, and agile tracking methods, supported by case studies and empirical literature. Key findings show that multi-layered frameworks improve adaptability, strengthen decision making, and enhance transparency. They also create a shared risk language across technical, managerial, and executive levels, which improves communication and coordination. Results reveal that challenges persist, including coordination complexity, cultural resistance, and potential duplication when frameworks are not harmonized. Addressing these issues requires deliberate integration planning, stakeholder engagement, and change management strategies. In addition, adopting AI and automation improves real-time risk detection, dynamic control mapping, and continuous monitoring. These capabilities help organizations maintain compliance and resilience in rapidly changing regulatory environments. In conclusion, multi layered risk management frameworks represent a strategic imperative for organizations operating in high tech sectors. By combining governance oversight, technical precision, and agile adaptability, these frameworks deliver resilience, foresight, and agility essential for sustainable growth and long term competitive advantage.